Non-functioning or underdeveloped right ventricle with intact ventricular septum - Ilgaz, Ayten (The Turkish Journal of Pediatrics, 1962)
From our observations it appeared that in any case of underdevelopment of the right ventricle, whatever the cause may be, the shift of the axis of the ventricular potentials toward the left can be expected, whether left ventricular hypertrophy is present or not.⁶ There is more shift of the axis to the left in the above mentioned Groups 1 and 2, than in Group 3.Cyanosis is usually present from birth. The mechanism of formation of this congenital anomaly is not yet known.The history, clinical, laboratory and pathological findings have been reviewed. In all cases the findings were confirmed by postmortem examinations.